2005
DOI: 10.1007/s00402-005-0809-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of parenteral iron in the management of anaemia in the elderly patient undergoing displaced subcapital hip fracture repair: preliminary data

Abstract: Preoperative parenteral iron administration could be a safe and effective way to reduce the ABT requirements in DSHF patients. This reduction in the ABT requirements is accompanied by a reduction in the morbid-mortality rate and LOS. A large, randomised, controlled trial to confirm these results is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 32 publications
9
108
3
2
Order By: Relevance
“…The RCT reported no effect of intravenous iron on transfusion to which the addition of observational data resulted in an association of intravenous iron with a reduced rate of blood transfusion, relative risk (95% CI) 0.66 (0.48-0.89), p = 0.007, a result unaffected by the exclusion of a study with higher risks of bias (Fig. 10) [52]. The RCT reported no effect of intravenous iron on the length of hospital stay.…”
Section: Tablementioning
confidence: 91%
See 1 more Smart Citation
“…The RCT reported no effect of intravenous iron on transfusion to which the addition of observational data resulted in an association of intravenous iron with a reduced rate of blood transfusion, relative risk (95% CI) 0.66 (0.48-0.89), p = 0.007, a result unaffected by the exclusion of a study with higher risks of bias (Fig. 10) [52]. The RCT reported no effect of intravenous iron on the length of hospital stay.…”
Section: Tablementioning
confidence: 91%
“…Three observational studies [44,49,52] reported no association of intravenous iron with mortality and one RCT [67] reported no effect of intravenous iron on mortality (Fig. 9).…”
Section: Tablementioning
confidence: 99%
“…iron can correct iron deficiency anaemia before elective orthopaedic surgery 67 and reduce rates of ABT, postoperative infection, and mortality in patients with hip fracture, compared with historical controls. 68 69 Another case series found that the perioperative use of i.v. iron in conjunction with ESA therapy in anaemic patients with hip fracture (Hb levels of ,13 g dl 21 ) reduced the proportion of patients requiring transfusion, the number of units transfused, and the rate of postoperative infections compared with a parallel control group.…”
Section: Patient Blood Managementmentioning
confidence: 99%
“…One option for reducing the need for transfusion in neck of femur patients may be the use of intravenous iron therapy or recombinant preoperative erythropoietin [18,19]. However, concerns exist for the potential for adverse drug reaction as well as the possible increased incidence of venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%